2020
DOI: 10.1016/j.heliyon.2020.e05776
|View full text |Cite
|
Sign up to set email alerts
|

A molecular scale analysis of TEMPO-oxidation of native cellulose molecules

Abstract: The native cellulose, through TEMPO (2,2,6,6-tetramethylpiperidine-1-oxyl radical)-mediated oxidation, can be converted into individual fibers. It has been observed that oxidized fibers disperse completely and individually in water. It is believed that electrostatic repulsive forces might be responsible for such observations. In order to study the TEMPO-oxidation of cellulose molecules, we used Density Functional Theory (DFT) calculations and Flory-Huggins theory combined with molecular dynamics (MD). The surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…24 Recent theoretical studies have shown that COO − groups in TOCN dispersions can cause a triple screw conformational change, increasing the repulsion between the cellulose particles and their hydrophilicity. 71 In our case, TOCN could potentially undergo conformational changes affecting the surface COO − density and the z potential value. Another factor to consider is the presence of silica (SiO 2 ) in the TOCN suspensions from the EFB matrix (Fig.…”
Section: Efb-tocn Size Distribution and Z Potentialmentioning
confidence: 72%
“…24 Recent theoretical studies have shown that COO − groups in TOCN dispersions can cause a triple screw conformational change, increasing the repulsion between the cellulose particles and their hydrophilicity. 71 In our case, TOCN could potentially undergo conformational changes affecting the surface COO − density and the z potential value. Another factor to consider is the presence of silica (SiO 2 ) in the TOCN suspensions from the EFB matrix (Fig.…”
Section: Efb-tocn Size Distribution and Z Potentialmentioning
confidence: 72%
“…Nevertheless, a previous study found that adding a significant number of sodium carboxylate groups to the surface of nanocellulose increases the possibility of aldehyde group formation. 160 Few studies of TEMPO-mediated oxidation techniques have been undertaken to address the compatibility issues between nanocellulose and polymer matrix. One of them employs the reaction condition of TEMPO/NaClO/NaBr at pH 10 in the presence of water.…”
Section: Physical Modificationmentioning
confidence: 99%
“…158,159 The generation of interfibrillar repulsive forces of dense surface charges causes individualization between fibrils, which aids in their liberation and retention in the stable colloidal form. 160,161 During the reaction, the C6 hydroxy groups (C6-OH) of nanocellulose (-CH 2 OH) preferentially oxidize to sodium carboxylate groups (-COONa). 132,161 The oxidation process of C6-OH groups initiates the dissociation of sodium atoms from -COONa, leaving the negatively charged carboxylate (-COO-) groups on TEMPO-oxidized nanofibrils, which later act as scaffolds, aiding in the assembly of the metal ions via an ion exchange process to increase nanocellulose functionalities.…”
Section: Source Of Nanocellulose From Natural Fibermentioning
confidence: 99%
See 1 more Smart Citation
“…Solving the above problem requires reliable insight into the interplay of 1) the critical raw material attributes, 2) the critical process parameters, and 3) the drug product’s critical quality attributes. This in turn necessitates models that utilize a bottom-up approach ( 32 , 33 ) [where the material properties are calculated from scratch using, e.g., density functional theory [DFT] and molecular dynamics [MD] ( 34 )] to establish a process design space without prior experimental information. After producing this design space, a process optimization strategy can be synthesized for any specific operational parameters.…”
mentioning
confidence: 99%